Influence of the external pressure on the quantum correlations of molecular magnets. (15th March 2017) - Cruz, C.; Alves, Á. S.; dos Santos, R. N.; Soares-Pinto, D. O.; de Jesus, J. C. O.; de Almeida, J. S.; Reis, M. S.
Abstract: The study of quantum correlations in solid-state systems is a large avenue for research and their detection and manipulation are an actual challenge to overcome. In this context, we show by using first-principles calculations on the prototype material KNaCuSi4 O10 that the degree of quantum correlations in this spin cluster system can be managed by external hydrostatic pressure. Our results pave the way for research in detection and manipulation of quantum correlations in magnetic systems with promising applications in quantum information science.